Physician Responses to Enhanced Prescription Drug Monitoring Program Profiles. Issue 2 (28th January 2019) - Leichtling, Gillian; Hildebran, Christi; Novak, Kevin; Alley, Lindsey; Doyle, Sheri; Reilly, Cynthia; Weiner, Scott G
Abstract: Objective: Many states have begun implementing enhancements to PDMP patient profiles such as summaries or graphics to highlight issues of concern and enhance comprehension. The purpose of this study was to examine how physicians respond to sample enhanced PDMP profiles based on patient vignettes. Design: Brief semistructured interviews with physicians. Setting: Three national medical conferences for targeted specialties. Subjects: Ninety-three physicians practicing in primary care, emergency medicine, or pain management. Methods: We presented participants with one of three patient vignettes with corresponding standard and enhanced PDMP profiles and conducted brief interviews. Results: Findings indicated that enhanced profiles could increase ease of comprehension, reduce time burden, and aid in communicating with patients about opioid risks. Physicians also expressed concern about liability for prescribing when the enhanced profile indicates risk and cautioned against any implication that risk warnings should override clinical judgment based on the patient's complete medical history or presenting condition. Physicians emphasized the need for transparency of measures and evidence of validation of risk scores. We found little indication that enhanced profiles would change opioid prescribing decisions, though decisions varied by physician. Conclusions: Our study underscores the importance of involving prescribers in developing and testing PDMP profile enhancements, as well as providing guidance in the interpretation and clinical use of enhanced profiles. Reduced time burden is an important benefit to consider as the number of states mandating PDMP use increases.